THE ANALYSIS OF QUALITY OF DOUGH FROM A COURSE OF THE HIGHER MATHEMATICS ON THE SUBJECT "LINEAR ALGEBRA, ANALYTICAL GEOMETRY" - Larisa V. Limanova; Lidiya Aleksandrovna Muratova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article the mathematico-statistical analysis of quality of dough on the subject "Linear Algebra, Analytical Geometry" is carried out. Quality of dough decides on the help of such characteristics as reliability, a validity and a diskriminativnost. At research of test for reliability three ways of calculation of coefficient of reliability were applied: on a variation of test tasks (formula KR-20); with use of average coefficient of correlation of all tasks among themselves (a formula of calculation of coefficients of correlation for dichotomizing data); splitting of dough on even and odd tasks and determination of coefficient of correlation between these groups. In the latter case the coefficient of reliability was corrected on Spirmena-Brown's formula. The analysis of results showed in all three cases satisfactory reliability of dough, as all turned-out reliability coefficients more than 0,7. The validity of dough was estimated by means of dot biserial coefficient of correlation - coefficient of correlation of each task with test point of the student (individual point) and the general coefficient of a validity of dough. It appeared that the general coefficient of a validity has average value (0,434). For improvement of quality of dough it is offered to exclude the tasks 1, 4 and 12 having or negative correlation with many other tasks, or too low correlation with test point of the student. The analysis of coefficients of a diskriminativnost also speaks well for an exception of the test of the specified tasks. In general it is possible to draw a conclusion that this test can be used as a control device of knowledge of students of the subject "Linear Algebra, Analytical Geometry" after the specified completion.